Cover Feature: Rational Design of a Uranyl Metal–Organic Framework for the Capture and Colorimetric Detection of Organic Dyes (Chem. Eur. J. 61/2020). Issue 61 (1st October 2020) - Surbella, Robert G.; Carter, Korey P.; Lohrey, Trevor D.; Reilly, Dallas; Kalaj, Mark; McNamara, Bruce K.; Schwantes, Jon; Abergel, Rebecca J.
Abstract : A new uranyl containing metal–organic framework was prepared and the diffraction data reveals the structure consists of interpenetrating 3D nets with a 4, 3‐connected tbo topology. Each net contains large 22.8 Å pores and is constructed from monomeric, hexagonal bipyramidal uranyl nodes that are joined by 1, 2, 4, 5‐tetrakis(4‐carboxyphenyl)benzene ligands. The crystalline material is stable in aqueous media and due to the large void space (constituting 76 % of the unit cell by volume) can sequester organic dyes, the uptake of which induces a visible change to the color of the material. More information can be found in the Full Paper by R. G. Surbella III et al. on page 13819 .